Tingkat Kemampuan Bahasa Inggris Dosen Vokasional di Politeknik Hasnur Banjarmasin berdasarkan Ujian TOEFL - Hamrani, Hamrani (INTELEKTIUM, 2024)
This study investigates the English proficiency levels of vocational lecturers at Hasnur Polytechnic in Banjarmasin, South Kalimantan. An analysis of their English proficiency is needed by measuring their TOEFL score. The researcher gave a TOEFL test to 25 lecturers as research subjects. TOEFL ability is mapped into the Common European Framework of Reference for Language (CEFR), measured at four different levels, namely A2, B1, B2, and C1. This research method is quantitative research design, and using a descriptive analysis. The objective is to identify proficiency levels and analyze of the vocational lecturers’ English skills. The results indicate a wide range of proficiency, with most lecturers falling within the Elementary level (A2), one lecturer at the basic user level, a smaller portion at the Intermediate level (B1), and there is no achieving Upper intermediate proficiency (B2) and advanced level (C1). This study provides insights into the current state of English language skills among vocational lecturers and highlights areas for potential improvement. The findings suggest the need for targeted language training programs to enhance English proficiency, which is essential for academic and professional development.